The Concept of Real Religiosity in Graham Greene’s The Heart of the Matter (Journal of the College of Languages (JCL), 2016)
Religion in its general and simplified form is defined as a set of values or moral laws, which include provisions that people should follow to organize their affairs and ratify that they are provisions sent from the divine. The concept of religion is not limited to the narrower sense represented by the performance of the virtual rituals of worship and religious fashions, etc., but also includes all the moral and spiritual values, conduct and good dealing that reflect the true essence of religion, which boils down to a set of values – such as sincerity, honesty and dedication to work, merciful dealing and compassion, etc. All religions agree on the moral content of religion. The Prophet of Islam, Muhammad (peace be upon him) said in a hadith that: “God does not look at your photos and money, but look into your hearts and your deeds”. As the Prophet Jesus (Isa in Islam) (peace be upon him) said: “blessed are those of the pure hearts, they bear witness to God.” However, in the present day religion is measured only by its external shape. Lots of thinkers and writers have rebelled against this narrow vision of religion and insisted that religion is an essence rather than appearance. Among these is the English writer and novelist Graham Greene (1904-1991) who, despite the stigma of atheism, did not stray far from the soul of religion. In his novel, The Heart of the Matter (1948) Greene tries, through his protagonist, to pinpoint what the heart of religion is.